2013
DOI: 10.1177/0218492313515498
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal muscle flap and intracostal suture to reduce post-thoracotomy pain

Abstract: these techniques lead to a reduction in the acute and chronic post-thoracotomy pain, without increasing complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Many anesthetic and pharmacological agents are used to decrease postthoracotomy pain. However, these drugs carry risks of side effects and control the postthoracotomy pain effectively [ 18 ]. Furthermore, a literature search suggests that acupuncture analgesia is more efficient in surgical patients when administered postoperatively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many anesthetic and pharmacological agents are used to decrease postthoracotomy pain. However, these drugs carry risks of side effects and control the postthoracotomy pain effectively [ 18 ]. Furthermore, a literature search suggests that acupuncture analgesia is more efficient in surgical patients when administered postoperatively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical techniques that protect the nerve bundle may mitigate acute pain, 1,49–58 persistent postoperative pain, 49,52–60 and analgesic consumption 49,56,59 as well as facilitate an earlier return to baseline activities 50,54,58,60 (Category A2 evidence1,49–52,54, 58,60 and Category B2 evidence 53,55,56 , 57,59 ). These include nerve-sparing thoracotomy incision, 1,59 closure with rib approximation, 51 intercostal muscle flap, 58,60 or no-compression suture techniques alone 52,53,56 or in combination 49–51,54,55,57 to avoid intercostal nerve compression or involvement. 1,49–60 However, some studies 61–63 showed that surgical technique has no influence on the incidence of acute or persistent postoperative pain after surgery (Category A2 evidence).…”
Section: Preoperative Evaluation Of Risk Factors For Pain and Opioid ...mentioning
confidence: 99%
“…These include nerve-sparing thoracotomy incision, 1,59 closure with rib approximation, 51 intercostal muscle flap, 58,60 or no-compression suture techniques alone 52,53,56 or in combination [49][50][51]54,55,57 to avoid intercostal nerve compression or involvement. 1,[49][50][51][52][53][54][55][56][57][58][59][60] However, some studies [61][62][63] showed that surgical technique has no influence on the incidence of acute or persistent postoperative pain after surgery (Category A2 evidence).…”
Section: Surgical Factors That Influence Acute And/ormentioning
confidence: 99%
“…This conclusion is supported by the work published by Sapkota and colleagues. 1 However, the completion of an intercostal flap for applying a separator combined with an intracostal suture provides no improvement in the control of acute or subacute pain regarding the intracostal suture technique without an intercostal flap (level of evidence grade A).…”
mentioning
confidence: 99%
“…We read with great interest the article by Sapkota and colleagues. 1 Their study, a randomized clinical trial, included 48 patients over a period of 15 months. Twenty-five patients were included in a control group, and underwent pericostal suture of intercostal space by the classic technique; 23 patients formed the study group, with suture of the intercostal space by an intracostal technique.…”
mentioning
confidence: 99%